Pengaruh Kompetensi SDM dan TI Terhadap Kualitas Laporan Keuangan Pada PT IBP Ledo, Bengkayang: Indonesia - Palija, Hizra; Jayanti, Fitri; Sari, Indah Purnama (Jurnal Keuangan dan Perbankan Syariah, 2024)
Investigating the impact of human resource competencies and information technology utilization on the quality of financial statements at PT IBP (Induk Bumi Perkasa), located in Ledo District, Bengkayang Regency. The approach used is descriptive with a quantitative approach, involving all employees of PT IBP as data sources. The amount of data obtained was 30 employees, with 26 of them being sampled using a questionnaire containing statements scored with predetermined scores. The results showed that the two factors studied, namely human resource competence (X1) and information technology utilization (X2), had a significant influence on the quality of financial statements (Y) at PT IBP (Induk Bumi Perkasa). This conclusion highlights the importance of the role of competent human resources and the proper use of information technology in improving the quality of the company's financial statements. Keyword : Human resource competence, information technology and financial report quality.